Experimental Measurements and Modeling of Vapor-Liquid Equilibrium of Isobutane and Ethyl Mercaptan Binary System - Neyrolles, Esther; Valtz, Alain; Boonaert, Eric; Coquelet, Christophe (International Journal of Petroleum Technology, 2021)
In this work, new isothermal experimental data of vapor-liquid equilibrium of the isobutane and ethyl mercaptan binary system are presented. The pressure and temperature conditions are up to 1 MPa and between 298 and 343K. The experimental apparatus is based on a “static-analytic method” specially developed for low-pressure measurements. Two online capillary samplers are used to take vapor and liquid samples that are analyzed with a gas chromatograph. The classical Peng Robinson Equation of State is used to correlate the experimental data. The van Ness test is used to check the consistency of the data. The measured data are also compared to predicted values from two predictive models, and a good agreement is found between the PSRK UNIFAC and the PPR78 models and the experimental measurements.